The Barley (Hordeum vulgare ssp. vulgare) Respiratory Burst Oxidase Homolog (HvRBOH) Gene Family and Their Plausible Role on Malting Quality - Mahalingam, Ramamurthy; Graham, Danielle; Walling, Jason G. (Frontiers in Plant Science, 2021)
Controlled generation of reactive oxygen species (ROS) is pivotal for normal plant development and adaptation to changes in the external milieu. One of the major enzymatic sources of ROS in plants are the plasma-membrane localized NADPH oxidases, also called as Respiratory Burst Oxidase Homologs (RBOH). In addition to the six previously reported, seven new members of RBOH gene family were identified in barley using in silico analysis. Conservation of genomic structure and key residues important for catalytic activity and co-factor binding was observed in barley RBOH genes. Phylogenetic analysis of plant RBOHs revealed distinct clades for monocot and dicot RBOH proteins. Hence, we propose to use the rice nomenclature for naming barley RBOH genes. Temporal changes in ROS profiles were observed during barley malting and was accompanied by changes in protein carbonylation, lipid peroxidation, and antioxidant capacity. Among the nine differentially expressed HvRBOHs during various malting stages, HvRBOHA and HvRBOHC showed most significant sustained changes in expression. RNAi knockdown lines with reduced expression of HvRBOHA/C gene exhibited genetic compensation via inducible expression of other gene family members during malting. However, the physiological consequence of reduced expression of HvRBOHA/C manifested as a poor malting quality profile attributable to low alpha-amylase activity and high levels of beta-glucan. We propose that the HvRBOHs play a critical role in modulating the redox milieu during the early stages of malting, which in turn can significantly impact carbohydrate metabolism.